PORTRAYING THE CONTENT IN THE TEXTBOOK ENTITLED “THINK GLOBALLY ACT LOCALLY” BASED ON CULTURAL VIEW - Syahputra, Dimas; El Walidayni Kau, Magvirah; Mamu, Rahmawaty (CV. Lafadz Jaya, 2025)
This qualitative study examines cultural representation in the Indonesian EFL textbook